Analysis of temperature adaptability of Eocanthecona furcellata (Wolff) (Hemiptera: Pentatomidae) based on age-stage, two-sex life table and predatory functional response - Lingyi Liu; Mengshuang Yao; Runa Zhao; Wenlong Chen (PLoS ONE, 2026)
Eocanthecona furcellata (Wolff) (Hemiptera: Pentatomidae) is a key natural predator of agricultural and forestry pests. In nature, temperature affects the growth, development and predation ability of predators. Therefore, this study assessed the growth, development, and reproduction of E. furcellata at 20, 23, 26, 29, and 32°C. Age-stage, two-sex life table analysis showed that the development duration of each stage decreased with increasing temperature. At 20°C, individuals reached adulthood but females did not oviposit. At 29°C, intrinsic and finite rates of increase and fecundity were higher, with values of 0.12, 1.13 and 41.59, respectively. Moreover, the mean generation time was relatively short at 29.98 d. Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) is a highly destructive invasive pest that causes severe economic losses to crops. Therefore, this study evaluated the potential of E. furcellata to control S. frugiperda by predation functional response and interference effects. The functional response of adults to fourth-instar larvae of S. frugiperda followed the Holling II equation across all tested temperatures. Predation ability ( a/T h ) and maximum daily predation ( 1/T h ) were the highest at 32°C (female: a/T h = 52.7149, 1/T h = 51.8135; male: a/T h = 46.2538, 1/T h = 44.8430), but adult search efficiency was negatively correlated with prey density. At constant prey density, search efficiency increased with temperature. Intraspecific competition and mutual interference were also observed among adults. Across temperatures and prey ratios, adults consistently exhibited strong predation preference for fourth-instar larvae of S. frugiperda . These results provide a theoretical basis for the practical use of E. furcellata in pest management.